A crystalline trianionic triangular triboron species - Feng, Zhongtao (2024)
Coulomb repulsion in multiply charged ions (MCIs) is mitigated by long-range electrostatic interaction with the distant charge separation and delocalized systems. Meanwhile, MCIs featuring the charged centers located at two directly connected atoms (E+/−–E+/−) bear a strong repulsive force, which leads to electron detachment or molecular fragmentation, namely, Coulomb explosion. Here, we describe the synthesis of a trianionic triangular triboron species (B3R63−) through the reductive dealumination from a Cp∗AlB3R6 anion (Cp∗, 1,2,3,4,5-pentamethylcyclopentadienyl). X-ray crystallographic and spectroscopic analyses with the aid of quantum chemical calculations reveal that despite the triply negatively charged skeleton, the B3 core is tightly held by electron-precise B–B bonds, overcoming Coulomb repulsion. In contrast to the extant electron-deficient triborate rings, this molecule exhibits reducing ability and nucleophilicity; thus, it undergoes not only electron transfer but also cyclization and salt metathesis reactions, demonstrating its trait as elusive (R2B−) and ([R2B]22−) surrogates.